Collaborative Study of a Proposed International Standard for Plasma Fibrinogen Measurement - Gaffney, Patrick J; Wong, M Y (Thrombosis and Haemostasis, 1992)
There is increased interest in the relationship between plasma fibrinogen levels and the incidence of coronary artery disease. The National Institute for Biological Standards and Control (UK) has completed a study to establish an International Standard for plasma fibrinogen. This study was conducted using a recommended assay procedure to measure the clottable material present in the proposed lyophilised Standard (coded 89/644). Twenty-two laboratories from nine countries took part in the study and analysis of the data allowed the calibration of 89/644 at 2.4 mg/ml clottable protein. Agreement with this figure was established in two laboratories using three or more different assays for plasma fibrinogen. Degradation studies of the proposed plasma fibrinogen Standard suggested that no loss of clottable protein was observed when the lyophilised material was stored at 20° C for 1 year.The Fibrinogen Sub-Committee of the ISTH (Amsterdam, The Netherlands, June 1991) supported the establishment of 89/644 as an International Standard. This collaborative study will be presented to the Expert Committee on Biological Standardisation of the World Health Organisation at their 1992 session. In the meantime 89/644 will be distributed as the proposed International Standard for plasma fibrinogen measurement containing 2.4 mg/ ml clottable protein.